Interpreting match performance in elite futsal: considerations for normalizing variables using effective time - Spyrou, Konstantinos; Ribeiro, João Nuno; Ferraz, António; Alcaraz, Pedro E.; Freitas, Tomás T.; Travassos, Bruno (Frontiers in Sports and Active Living, 2023)
This study aimed to investigate the physical and individual technical-tactical performance of elite futsal players. Thirteen National Team futsal players (27.4±4.7 years, 70.3±7.6 kg, 176.3±5.5 cm) competed in 15 official matches in three distinct competitions. Session rate of perceived exertion (sRPE) and player load (PL) were measured for assessing physical internal and external load, respectively. Individual tactical actions were analyzed using Instat Scout ® , considering variables such as fouls, shots, shots on target, goals, successful dribbles, passes, successful passes, ball losses, ball recoveries, and challenges won. The cluster analysis classified the players into two groups: "highinvolvement" (HIGH) and "low-involvement" (LOW), based on their average effective playing time, sRPE, and PL. A linear mixed model was used to examine the differences in external and internal load and technical-tactical variables between the two groups, accounting for individual repeated measures. Considering absolute values, HIGH players presented higher sRPE, total PL, shots, goals, passes, successful passes, ball losses and recoveries, and challenges won (p = 0.001-0.039; ES = 0.43-2.48), when compared to their LOW counterparts. However, when analyzed relative to effective time, LOW players reached higher total PL and shots per minute (p = 0.001-0.012; ES = 0.39-0.93) when compared to HIGH players. Non-significant differences were found for the rest of the variables. In summary, these results emphasize the importance of normalizing internal and external load variables and technical-tactical performance variables per effective playing time in futsal. The 2 This is a provisional file, not the final typeset article current findings indicate that players with lower involvement can present the same or even higher physical and technical-tactical performance compared to teammates with more playing time.